2006
DOI: 10.1177/0269881106060967
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol monotherapy for treatment-resistant schizophrenia

Abstract: Cannabidiol (CBD), one of the major products of the marijuana plant, is devoid of marijuana's typical psychological effects. In contrast, potential antipsychotic efficacy has been suggested based on preclinical and clinical data (Zuardi et al., 2002). In this report, we further investigated the efficacy and safety of CBD monotherapy in three patients with treatment-resistant schizophrenia (TRS). This was an in-patient study. All patients were given placebo for the initial 5 days, and from the 6th to 35th day (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
2
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 21 publications
8
107
2
10
Order By: Relevance
“…More recently, CBD was administered to three schizophrenic patients who had not responded to typical antipsychotic drugs. 70 A partial improvement was observed in one patient, but only slight or no improvement in the other two, thus suggesting that CBD has little effect in patients resistant to typical antipsychotics. Confirming the suggestion of case-studies, a preliminary report from a 4-week double-blind controlled clinical trial, using an adequate number of patients and comparing the effects of CBD with amisulpride in acute schizophrenic and schizophreniform psychosis, showed that CBD significantly reduced acute psychotic symptoms after 2 and 4 weeks of treatment when compared to baseline.…”
Section: Antipsychotic Actionmentioning
confidence: 97%
“…More recently, CBD was administered to three schizophrenic patients who had not responded to typical antipsychotic drugs. 70 A partial improvement was observed in one patient, but only slight or no improvement in the other two, thus suggesting that CBD has little effect in patients resistant to typical antipsychotics. Confirming the suggestion of case-studies, a preliminary report from a 4-week double-blind controlled clinical trial, using an adequate number of patients and comparing the effects of CBD with amisulpride in acute schizophrenic and schizophreniform psychosis, showed that CBD significantly reduced acute psychotic symptoms after 2 and 4 weeks of treatment when compared to baseline.…”
Section: Antipsychotic Actionmentioning
confidence: 97%
“…Symptom worsening was observed when the administration was interrupted. In another case study, CBD was administered to three 22-or 23-year-old male schizophrenic patients who had not responded to typical antipsychotic drugs for 30 days [104]. The dose of CBD was increased from 40 up to 1280 mg d 21 .…”
Section: Cannabidiol and Psychosismentioning
confidence: 99%
“…CBD also possesses antipsychotic properties [2,[57][58][59][60][61]. Not surprisingly, and as witnessed in the aforementioned preclinical data, CBD has been shown to reduce anxiety in patients with social phobia and generalized social anxiety disorders [62][63][64].…”
Section: Cbd and Neurobiological Targets/effectsmentioning
confidence: 99%